Perceptual learning in the chemical senses: A review. (September 2019) - Spence, Charles
Abstract: People have been writing about perceptual learning and expertise in the chemical senses for more than a century now, with a particular focus on the world of wine. However, the problem with many of the cross-sectional studies of wine expertise that have been published to date is that they simply cannot rule out the possibility that those with superior chemosensory abilities end-up gravitating toward a career in wine. Definitions of expertise also tend to vary widely between studies, making direct comparison of the results obtained rather difficult. By contrast, the longitudinal learning studies that have been published have typically only assessed the effects of relatively small amounts of training. And, taken as a whole, the majority of studies in this area tend to look statistically underpowered nowadays in terms of the sample sizes that have been used. Nevertheless, despite these limitations, the literature converges on the conclusion that chemosensory perceptual learning does occur, though the gains (e.g., in terms of lower detection thresholds) are usually modest at best, and tend to be highly stimulus-specific. By contrast, cognitive/semantic improvements in describing/discriminating wines, and wine-relevant compounds, as well as the acquisition of relevant conceptual knowledge, are much more salient differentiators in the cross-sectional empirical literature. Enhanced attention and olfactory recognition memory abilities have also been reported amongst wine experts. Looking to the future, the hope is that the insights garnered from studies of perceptual learning in the higher spatial senses may help to optimize the training regimes for those wishing to enhance their wine-tasting abilities, and perhaps also aid recovery in those suffering from olfactory loss. Highlights: Perceptual learning is a key component of expertise (e.g., in the chemical senses). To date, most research on perceptual learning has focused on the spatial senses. Cross-sectional and longitudinal studies of chemosensory perceptual learning are reviewed. The evidence suggests that perceptual benefits, when they occur, are stimulus specific. Majority of studies of chemosensory perceptual learning underpowered.